Morphological characterisation of selected African accessions of bambara groundnut (Vigna subterranea (L.) verdc.) - Atoyebi, J.O.; Oyatomi, Olaniyi; Osilesi, O.; Adebawo, O.; Abberton, Michael T. (Scientific and Academic Publishing, 2017)
Three hundred (300) accessions of Bambara groundnut (Vigna subterranea (L.) Verdc) among the 1973 maintained in the global repository at the International Institute of Tropical Agriculture (IITA), Ibadan, genebank were selected for this study. Two to three seeds of each accession were planted during the 2014 / 2015 planting season at IITA, Ibadan, Nigeria. Seedlings were thinned to a single plant prior to flowering. Thirty - seven (37) agro-morphological parameters, representing 28 quantitative and 9 qualitative traits were recorded on each plant (IPGRI, 2000). The data were subjected to analysis using the statistics application system (SAS) software, version 9.3, both to depict correlation among parameters and eigen values with principal component on scree plot and dendrogram construction. The results revealed lines (e.g TVSu – 293, TVSu – 395, TVSu – 1243) that had high yield potentials. Also, TVSu -397 and TVSu – 1168 had the highest number of leaves while TVSu – 520 and TVSu – 1022 had the least. The least number of seeds per plant was given by TVSu – 1, TVSu – 353 and TVSu – 454, while TVSu – 395, TVSu – 618 and TVSu – 1897 gave the highest number of seeds at harvest. The result provides information necessary for future nutrition and breeding studies on Bambara groundnut and its improvement.